FACTOR ANALYSIS APPROACH-TAGUCHI-PARETO METHOD TO CASTING A356 ALLOY COMPOSITE FOR LIGHTWEIGHT WHEEL RIM COVER OF VEHICLES - Stephen Chidera Nwafor; Sunday Ayoola Oke; Chris Abiodun Ayanladun (Jurnal Ilmiah Teknik Industri, 2022)
The aspect of reinforcing re-usable A356 alloys with organic matters is a principal, success yet expanding in scope regarding new products development. Despite, the use of Taguchi-Pareto method has potentials for improvement. The purpose of this article is to examine the factor analysis- Taguchi-Pareto method at which identification of the key factors could be achieved while concurrently optimizing the factors. The point of integration is at the variance determination of the unrotated factor loadings and communality. The synergy between factor analysis and Taguchi-Pareto method provides practical assistance to foundry engineers to concurrently select key factors while optimising them. The factors were noted to be effective and responsive to the proposed method. The delta values are 0, 0.84 and 0 for LC1, WC1 and HC1, respectively while the ranks are WC1 as first while the second position is shared between LC1 and HC1. The optimal parametric settings are LC11 WC11 HC11, LC11 WC11 HC12, LC12 WC11 HC11 or LC12 WC11 HC12. One of the optimal parametric settings is 0.280m of LC1 with 1.788kg of WC1 and 0.036m of HC1. The finding provides novel steps to the concurrent factor identification and optimisation in the choice of optimal parametric setting for the process. It is the first step towards sustainable foundry practice.